An Updated Narrative Review on Dengue (Green Life Medical College Journal, 2025)
Dengue fever (DF) is a mosquito-borne viral illness that has spread rapidly throughout the world in recent years. Dengue virus is primarily transmitted by female mosquitoes (Aedes aegypti) species and also by (Aedes Arbopictus). Symptoms are usually flu-like but can progress to severe dengue haemorrhagic fever, a life-threatening condition. The incidence of DF has increased dramatically over the past few decades. The true number of dengue cases is underestimated because the vast majority of infected patients are asymptomatic or with mild and self-limited disease. Many patients were misdiagnosed to be other febrile illnesses. It is estimated that 2.5 billion people are at risk of having the disease, making dengue fever a major international public health concern. This review provides insights on dengue fever transmission, complications, treatment and impact on the healthcare system.Journal of Green Life Med. Col. 2025; 10(2): 58-61